Diet Quality Is Associated With Mortality in Adults Aged 80 Years and Older: A Prospective Study. Issue 10 (6th August 2019) - Liu, Yi‐Hsuan; Gao, Xiang; Mitchell, Diane C.; Wood, G. Craig; Still, Christopher D.; Jensen, Gordon L.
Abstract : OBJECTIVES: Diet quality has been associated with health outcomes and quality of life. However, the association between diet quality and mortality in older people, those aged 80 years and older, is understudied. Therefore, we conducted a prospective study to examine whether better diet quality, assessed by a validated dietary screening tool (DST), was associated with lower mortality in those aged 80 years and older. METHODS: Our study included 1990 participants (812 men and 1178 women), with a mean age of 84.1 years at baseline (ranging from 80 to 102 years old), from the Geisinger Rural Aging Study longitudinal cohort in Pennsylvania. Baseline descriptive information was obtained in 2009, and the DST was administered via mailed survey. The DST is composed of 25 food‐ and behavior‐specific questions associated with dietary intake that generate a diet quality score ranging from 0 (lowest) to 100 (highest). Death was identified using electronic medical record and the Social Security Death Index data. Hazard ratios (HRs) and 95% confidence intervals (CIs) across three diet quality categories were calculated by using Cox proportional hazards models after adjusting for potential confounders. RESULTS: Over 8 years of follow‐up (October 2009‐February 2018), 931 deaths were documented. Higher diet quality was associated with lower mortality risk ( P ‐trend = .04). Participants with high diet quality (defined as DST scores >75) had significantly lower risk of mortality compared with those with low diet quality (defined as DST scores <60) after adjusting for potential risk factors (adjusted HR = 0.76; 95% CI = 0.59‐0.97). CONCLUSION: Diet quality, assessed by DST, is significantly associated with risk of mortality in older adults aged 80 years and older in our prospective cohort. Our results indicate that nutrition may have an important role in healthy aging, and more studies are needed to develop appropriate dietary recommendations for older persons. J Am Geriatr Soc 67:2180–2185, 2019